Ghdhdjhdd dududbribrrh tiene en 73839933
A. 4x + 9 = 34
<u> - 9 - 9</u>
<u>4x</u> = <u>25</u>
4 4
x = 6.25
B. (x - 4)(x + 2) = 0
x - 4 = 0 U x + 2 = 0
<u> + 4 + 4</u> <u> - 2 - 2</u>
x = 4 x = -2
C. 2x² - 6x + 4 = 0
2(x²) - 2(3x) + 2(2) = 0
<u>2(x² - 3x + 2)</u> = <u>0</u>
2 2
x² - 3x + 2 = 0
x = <u>-(-3) +/- √((-3)² - 4(1)(2))</u>
2(1)
x = <u>3 +/- √(9 - 8)</u>
2
x = <u>3 +/- √(1)
</u> 2<u>
</u> x =<u> 3 +/- 1
</u> 2
x = <u>3 + 1</u> U x = <u>3 - 1</u>
2 2
x = <u>4</u> x = <u>2</u>
2 2
x = 2 x = 1
<u />
1) is ABC and XYZ
2) is ABC and RQP I’m not sure about this one though
Answer:
the answer is 5
Step-by-step explanation:
Answer:
Let's solve for f.
fx=
4x−3
x−10
Step 1: Multiply both sides by x-10.
fx2−10fx=4x−3
Step 2: Factor out variable f.
f(x2−10x)=4x−3
Step 3: Divide both sides by x^2-10x.
f(x2−10x)
x2−10x
=
4x−3
x2−10x
f=
4x−3
x2−10x
Answer:
f=
4x−3
x2−10x
Let's solve for g.
gx=
2x−8
x−10
Step 1: Multiply both sides by x-10.
gx2−10gx=2x−8
Step 2: Factor out variable g.
g(x2−10x)=2x−8
Step 3: Divide both sides by x^2-10x.
g(x2−10x)
x2−10x
=
2x−8
x2−10x
g=
2x−8
x2−10x
Answer:
g=
2x−8
x2−10x
Step-by-step explanation: